9A.03: OSTEOPONTIN AND OSTEOPROTEGERIN ACTIVATE MONOCYTES INTO ANTI-INFLAMMATORY PROPERTIES IN THE PATIENTS WITH HYPERTENSION-RELATED VASCULAR CALCIFICATION. (June 2015) - Ge, Q.; Ruan, C.; Gao, P.; Ma, Y.; Zhu, D.; Wang, J.
Abstract : Objective: Monocytes/macrophages are believed to play roles in vascular calcification(VC). Here, we analyzed whether osteopontin(OPN) and osteoprotegerin(OPG) might exert effects by promoting macrophage polarization into an anti-inflammatory phenotype in the patients with hypertension(HT)-related VC. Figure. No caption available. Design and method: In this study, 412 HT patients with or without VC were identified by using artery electronic calculators tomography(fig 1). Histological analysis was performed in the samples of aortic blood vessel from calcified vessels. Human peripheral blood CD14+ monocytes including M1∼like CD11c+ and M2∼like CD163+ cells were analysised by flow cytometery. The effects on M1 and M2 macrophages corrlated with cytokines and chemokines were assessed by qPCR. Results: We show that in HT patients, VC was correlated with higher systolic pressure, the higher incidence and more intima-media thickness of the plaque of carotid artery and was associated with arterial stiffness(including higher carotid-femoral pulse wave velocity, aortic systolic pressure, augment pressure, augment index(P < 0.05)). Furthermore, The phenotype of M1∼like monocyte/macrophages was significantly increasesd in HT patients with VC (P < 0.05)(Fig 3). Although both Serum OPN and OPG levels increased in HT patients with VC, they significantly upregulated anti-inflammatory M2 macrophages marks (P < 0.05) and only OPN downregulated pro-inflammatory M1 macrophages marks. Conclusions: The phenotype of M1 macrophages and M2 macrophages is promoted by VC(fig 2). The ability of OPN and OPG to promote differentiation of macrophages into an alternative, anti-inflammatory phenotype may explain their protective effects in VC of HT patients. These data provide novel insight into the link between inflammtion and VC diseases.